2020
DOI: 10.3390/cancers12102757
|View full text |Cite
|
Sign up to set email alerts
|

AXL Inactivation Inhibits Mesothelioma Growth and Migration via Regulation of p53 Expression

Abstract: Malignant mesothelioma is a locally aggressive and highly lethal neoplasm. Dysregulation and activation of Gas6/AXL tyrosine kinase signaling are associated with mesothelioma progression, but the mechanisms of these AXL tumorigenic roles are poorly understood. p53 mutants in lung carcinoma upregulate AXL expression by binding and acetylating the AXL promoter. Although TP53 mutations are uncommon in mesothelioma, we hypothesized that these tumors might have alternative feedback mechanisms between AXL and p53. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Nuclear AXL has been observed in various carcinomas, including schwannoma, melanoma, and mesothelioma (36-39); however, there is still more to interrogate regarding the function of nuclear AXL, especially in relation to EMT. One study identified in mesothelioma that there was nuclear colocalization of AXL and p53, and that AXL can bind to the TP53 promoter to suppress expression (39). Several AXL inhibitors are in clinical trials for advanced solid tumors, colorectal cancer, non-small cell lung cancer, and other diseases (ClinicalTrials.gov).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear AXL has been observed in various carcinomas, including schwannoma, melanoma, and mesothelioma (36-39); however, there is still more to interrogate regarding the function of nuclear AXL, especially in relation to EMT. One study identified in mesothelioma that there was nuclear colocalization of AXL and p53, and that AXL can bind to the TP53 promoter to suppress expression (39). Several AXL inhibitors are in clinical trials for advanced solid tumors, colorectal cancer, non-small cell lung cancer, and other diseases (ClinicalTrials.gov).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signaling proteins have been shown to impact PM migration. These include, for instance, the receptor tyrosine kinase (RTK) family member AXL [ 31 ], the RTK family ligands FGF2 and EGF [ 26 ], the TGFβ family members activin A and B [ 32 , 33 ] and the sheddase ADAM10 [ 34 ]. Here we demonstrate that YB‐1 is a key player in PM cell motility, which is in line with its role in several other malignancies including melanoma [ 35 ], sarcoma [ 36 ] and lung adenocarcinoma [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some of these genes out of the models were also directly associated with the MPM, which were mainly regarded as potential therapeutic targets, including CHEK1, DNMT3B, AXL, PAPPA, and miR-302b. Previous studies suggested that these genes are involved in the multiple antineoplastic processes of MPM, such as relief of chemo-and radioresistance, anti-proliferation, inhibition of growth and migration, and induction of apoptosis (31,(43)(44)(45)(46)(47)(48). Only two small-molecule drugs aiming to target the identified genes have been preliminarily evaluated, including palbociclib targeting CDK6 and AZD1775 targeting WEE1.…”
Section: Discussionmentioning
confidence: 99%